SOME RESULTS OF COST ANALYSIS IN INDUSTRIAL DISTRIBUTION. - Lowles, D. C. (The Accounting Review, 1931)
Abstract The article presents comments by scholar E.W. McCul on the survey on "Cost Accounting for Distribution by the Manufacturer," conducted by the Department of the Chamber of Commerce of the U.S. in the fall of 1929. The margin between the sales price and the cost of manufacture has frequently been the subject of criticism. This criticism arises from the assumption that costs in the marketing operations are too high. Those who undertake to analyze this statement are immediately confronted with the necessity for defining the phrase too high. How can it be known definitely that a cost is too high, unless there be a basis of cost that is not too high, in short, a basis that may be accepted as standard? A second question naturally follows. How can such a standard be set up, unless there be definite specifications on which it is predicated? The technique of cost accounting for distribution seems not to have reached that state of development that cost accounting for manufacture has reached. For this reason, possibly, knowledge of distribution costs is not as adequate as knowledge of costs of manufacture.